The census evaluation of competencies in Bogota : What does the school propose? - Jurado Valencia, Fabio (Rastros Rostros, 2023)
The school necessarily presupposes the change from the outside space - the street, the house - to an interior space, from inside corridors, courtyards and classrooms.